Development, Factor Structure, and Psychometric Validation of the Impostor Phenomenon Assessment: A Novel Assessment of Impostor Phenomenon - Walker, Deanna L.; Saklofske, Donald H. (Assessment (Odessa, Fla.), 2023)
Despite growing attention surrounding impostor phenomenon (also known as “imposter syndrome”), recent reviews have suggested that current measures may be inadequate in capturing the complex and multifaceted nature of this construct. The objective of the current studies was to clarify the theoretical conceptualization of impostor phenomenon based on experiences in an achievement-oriented setting. We conducted a review of the literature and developed an item pool for a novel impostor phenomenon assessment (IPA) (Study 1). Exploratory factor analyses (Study 1) and confirmatory factor analyses (Study 2) assessed this initial item pool to determine the factor structure and initial psychometric properties of the preliminary IPA (Studies 2 and 3). Our findings offer preliminary evidence for the reliability and validity of the IPA as a novel measure of impostor phenomenon.